Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.4037/ccn2012225
|View full text |Cite
|
Sign up to set email alerts
|

Hearing Loss in Older Critical Care Patients: Participation in Decision Making

Abstract: IncidenceHearing loss is the third most common chronic-condition disability Older adults with hearing loss who receive care in the noisy environment of a critical care unit can be disadvantaged in their ability to understand speech, thus limiting their participation in decision making. Providing optimal outcomes for such patients can be understood through use of the American Association of Critical-Care Nurses Synergy Model. When older adults are admitted to a critical care unit, their spouses, children, and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…No experimental evidence is available regarding the comparison between the Synergy Model and other PCC models. However, the novelty of Synergy Model is the focus aimed at linking patient's characteristics and nursing competencies, acknowledging that the Synergy Model conceptualizes as a continuum the eight nursing competencies and patients' characteristics: the synergy is achievable when the needs of patients are adequately matched with nurse's competencies (Kaplow 2003;Kaplow & Reed 2008;Hardin 2012b;Hardin 2015;Kaplow & Reed, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…No experimental evidence is available regarding the comparison between the Synergy Model and other PCC models. However, the novelty of Synergy Model is the focus aimed at linking patient's characteristics and nursing competencies, acknowledging that the Synergy Model conceptualizes as a continuum the eight nursing competencies and patients' characteristics: the synergy is achievable when the needs of patients are adequately matched with nurse's competencies (Kaplow 2003;Kaplow & Reed 2008;Hardin 2012b;Hardin 2015;Kaplow & Reed, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Synergy Model was also described as a useful framework to enhance the quality of the relationship between nurses and patients, which is reflected in improved patient-related outcomes (Tejero 2012). Hardin identified which strategies were useful to facilitate family participation in decision-making, improving patient safety and satisfaction (Hardin 2012b). In another study, the work climate improvements, derived by the Synergy Model's implementation, were reflected in lower rates of nosocomial infections and patient falls (Rozdilsky & Alecxe 2012).…”
Section: Patient-related Outcomesmentioning
confidence: 99%
“…Inpatients with hearing loss are at an increased risk for miscommunications because of adverse noise conditions in the typical hospital listening environment. 4,[22][23][24] Pope et al conducted a study on inpatients at a veterans hospital, examining patients' ability to identify and recall high-context and low-context speech against a background of simulated hospital noise. 25 Results showed that patients with hearing loss may have less success in hearing, understanding, and remembering new information in the hospital compared to those with normal hearing.…”
Section: Potential Impact Of Hearing Loss In the Hospital Environmentmentioning
confidence: 99%
“…Despite the high prevalence of hearing loss in older adults, the condition remains largely unrecognized and underappreciated in older adults across community settings and potentially during hospital stays. [4][5][6] Along with prevalence data on this population, there is a growing literature describing the varied effects of untreated hearing loss on an individual's function and potential for successful aging. Hearing loss negatively impacts psychosocial health and cognitive functioning.…”
mentioning
confidence: 99%
“…With an increasing ICU survival rate even for very complicated disease states such as sepsis, the ICU community is becoming more and more aware of post-ICU sequelae, also referred to as post-intensive care syndrome (PICS) [11]. In addition to ICU-acquired weakness and cognitive impairment, even a small deterioration in visual abilities may be very relevant for daily life activities, especially in the frail elderly with a pre-existing decline in function of potentially all six senses prior to and after ICU admission [12]. …”
mentioning
confidence: 99%